Morphological and molecular characterization of the Makran Glossogobius cf. giuris (Teleostei: Gobiidae) and the Glossogobius giuris species complex taxonomy - Zarei, Fatah; Kovačić, Marcelo; Esmaeili, Hamid Reza; Ghanbarifardi, Mehdi (Zootaxa, 2023)
The Indo-West Pacific Glossogobius giuris (Hamilton, 1822) species complex has four spatially circumscribed independent lineages, partially taxonomically resolved. A sample of gobies from the G. giuris species complex was recently collected from the Makran River System, south-eastern Iran, which drains into the northern Oman Sea. The taxonomic status of this population was clarified using a molecular and morphological framework. Molecular and morphological data both revealed that the examined sample from the Makran River System is conspecific with G. giuris B which is widely distributed in the coastal habitats and basins of the Indian Ocean. In addition, consensus from different molecular species delimitations, K2P genetic distance, and tree topologies confirmed the four lineages of the G. giuris species complex as distinct taxonomic entities, hereby highlighting the necessity of an integrative morphological and molecular approach to complete the clarification of taxonomic diversity within this group. Glossogobius giuris species complex taxonomy is discussed and solution recommended.